Stakeholder Involvement in Implementing CHSE-Based Health Protocol in Penglipuran Tourism Village - Putu Yunita Wacana Sari; Komang Again Pretty Teja Sari; Ni Wayan Wahyu Astuti (International Journal of Glocal Tourism, 2023)
Purpose: This study aims to identify the implementation and analyze the extent of stakeholder involvement in the implementation of the CHSE-based health protocol in Penglipuran Tourism Village, Bangli Regency, Bali, Indonesia. Research methods: Data collection methods were in-depth interviews, observation, and documentation. The technique for determining informants used a purposive sampling technique with qualitative data analysis techniques. Findings: CHSE-based health protocol in Penglipuran Tourism Village was implemented based on a guidebook from the government where, the implementation of the CHSE was divided into several zones which were considered crucial because there was direct contact with tourism actors, namely, homestay zones/tourist cottages, home zones dining, souvenir shop zones, and cultural zones that have been implemented properly by tourism entrepreneurs and tourists so that they are CHSE certified. Stakeholders involved in implementing CHSE are divided into three, namely: Primary Stakeholders (Tourism Managers) act as Coordinators and Facilitators, then (Tourism Entrepreneurs and Local Communities) as Implementers; Key Stakeholders (Kelian Adat/ Head of the area) act as Policy Creator, Coordinator and Accelerator; Secondary Stakeholders (Tourism and Culture Office) play a passive role as Facilitators. Implication: This research is expected to be a consideration for tourism entrepreneurs to work together with the government and the community to participate in implementing CHSE-based health protocols, as well as provide information regarding the involvement of tourism entrepreneurs who are able to have a positive influence on the progress of Penglipuran Tourism Village in carrying out tourism activities in pandemic period.